Microfluidic Microbial Bioelectrochemical Systems: An Integrated Investigation Platform for a More Fundamental Understanding of Electroactive Bacterial Biofilms - Stéphane Pinck; Lucila Martínez Ostormujof; Sébastien Teychené; Benjamin Erable (Microorganisms, 2020)
It is the ambition of many researchers to finally be able to close in on the fundamental, coupled phenomena that occur during the formation and expression of electrocatalytic activity in electroactive biofilms. It is because of this desire to understand that bioelectrochemical systems (BESs) have been miniaturized into microBES by taking advantage of the worldwide development of microfluidics. Microfluidics tools applied to bioelectrochemistry permit even more fundamental studies of interactions and coupled phenomena occurring at the microscale, thanks, in particular, to the concomitant combination of electroanalysis, spectroscopic analytical techniques and real-time microscopy that is now possible. The analytical microsystem is therefore much better suited to the monitoring, not only of electroactive biofilm formation but also of the expression and disentangling of extracellular electron transfer (EET) catalytic mechanisms. This article reviews the details of the configurations of microfluidic BESs designed for selected objectives and their microfabrication techniques. Because the aim is to manipulate microvolumes and due to the high modularity of the experimental systems, the interfacial conditions between electrodes and electrolytes are perfectly controlled in terms of physicochemistry (pH, nutrients, chemical effectors, etc.) and hydrodynamics (shear, material transport, etc.). Most of the theoretical advances have been obtained thanks to work carried out using models of electroactive bacteria monocultures, mainly to simplify biological investigation systems. However, a huge virgin field of investigation still remains to be explored by taking advantage of the capacities of microfluidic BESs regarding the complexity and interactions of mixed electroactive biofilms.